Epidemiology, Risk Factors and Measures for Preventing Drowning in Africa: A Systematic Review - Lauren Miller (Medicina, 2019)
Background and Objectives: Drowning is a leading cause of unintentional injury related mortality worldwide, and accounts for roughly 320,000 deaths yearly. Over 90% of these deaths occur in low- and middle-income countries with inadequate prevention measures. The highest rates of drowning are observed in Africa. The aim of this review is to describe the epidemiology of drowning and identify the risk factors and strategies for prevention of drowning in Africa. Materials and Methods: A review of multiple databases (MEDLINE, CINAHL, PsycINFO, Scopus and Emcare) was conducted from inception of the databases to the 1st of April 2019 to identify studies investigating drowning in Africa. The preferred reporting items for systematic review and meta-analysis (PRISMA) was utilised. Results: Forty-two articles from 15 countries were included. Twelve articles explored drowning, while in 30 articles, drowning was reported as part of a wider study. The data sources were coronial, central registry, hospital record, sea rescue and self-generated data. Measures used to describe drowning were proportions and rates. There was a huge variation in the proportion and incidence rate of drowning reported by the studies included in the review. The potential risk factors for drowning included young age, male gender, ethnicity, alcohol, access to bodies of water, age and carrying capacity of the boat, weather and summer season. No study evaluated prevention strategies, however, strategies proposed were education, increased supervision and community awareness. Conclusions: There is a need to address the high rate of drowning in Africa. Good epidemiological studies across all African countries are needed to describe the patterns of drowning and understand risk factors. Further research is needed to investigate the risk factors and to evaluate prevention strategies.